Quality-Based Payment for Medical Groups and Individual Physicians - James C. Robinson; Stephen M. Shortell; Diane R. Rittenhouse; Sara Fernandes-Taylor; Robin R. Gillies; Lawrence P. Casalino (SAGE Publishing, 2009)
This paper measures the extent to which medical groups experience external pay-for-performance incentives based on quality and patient satisfaction and the extent to which these groups pay their primary care and specialist physicians using similar criteria. Over half (52%) of large medical groups received bonus payments from health insurance plans in the period 2006-2007 based on measures of quality and patient satisfaction. Medical groups facing external pay-for-performance incentives are more likely to pay their primary care physicians (odds ratio [OR] 4.5; p<.001) and specialists (OR 2.5; p=.07) based on quality and satisfaction. Groups facing capitation payment incentives to control costs are more likely to pay member physicians on salary and less likely to pay based on productivity (p<.001 for primary care; p<.05 for specialists) than groups paid by insurers on a fee-for-service basis.